2020
DOI: 10.1155/2020/8895176
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Embedded Systems Remotely via Internet-of-Things Based on Emotional Recognition

Abstract: Nowadays, much research attention is focused on human–computer interaction (HCI), specifically in terms of biosignal, which has been recently used for the remote controlling to offer benefits especially for disabled people or protecting against contagions, such as coronavirus. In this paper, a biosignal type, namely, facial emotional signal, is proposed to control electronic devices remotely via emotional vision recognition. The objective is converting only two facial emotions: a smiling or nonsmiling vision s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…IOT has been used in many ways. IOT has been used in a smart grid control [1], emotional detection [2], smart home [3] and smart controlling [4]. The most used communication method between IOT devices and the server are api and websocket.…”
Section: Introductionmentioning
confidence: 99%
“…IOT has been used in many ways. IOT has been used in a smart grid control [1], emotional detection [2], smart home [3] and smart controlling [4]. The most used communication method between IOT devices and the server are api and websocket.…”
Section: Introductionmentioning
confidence: 99%
“…As it is noted, embedded systems can be controlled remotely via the Internet of Things (IoT), as in the reference [17]. This control is performed by any signal or image after being analyzed and understood by the smart system.…”
Section: Introductionmentioning
confidence: 99%
“…With this advantage, we have proposed a conceptual framework and device that utilizes the power of the deep learning (DL) algorithm for analyzing the non-invasive blood pressure sensor data and computer vision data for accurate FER of an individual [14]. The idea of implementing the DL algorithm in the edge device with a neural computing stick is to establish a resource-constrained portable device that detects the FER with a cost-effective real-time scenario [15]. A conceptual framework of the proposed study is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%